Study the Effect of Folic Acid as A supplement on Selected Oxidative Stress and Biochemical Parameters in First Trimester of Pregnancy - A. Mehde, Atheer; F. Ali, karima; A. Mehdi, Wesen (Iraqi Journal of Pharmaceutical Sciences, 2017)
Folic acid modulates several disorders in humans, pregnancy mostly because of the mitochondria-rich placenta, is a condition that favors oxidative stress.Transitional metals, especially iron, which are particularly abundant in the placenta, are important in the production of free radicals. Adenosine deaminase (ADA), an enzyme essential for the differentiation of lymphoid cells, has been used for monitoring diseases with altered immunity. In the present study we investigated the effect of regular and irregular administered folic acid in the first and second trimester of pregnancy to be compared with non-pregnant women ,and also the effect of regular and irregular using of folic acid supplement on oxidative stress parameters and several biochemical features in first trimester pregnant women. Methods :The Hemoglobin ,Random plasma glucose, transferrin, iron, adenosine deaminase in addition to antioxidants(Total antioxidant capacity (TAC), Glutathione (GSH), Glutathione peroxidase (GSH-Px), Glutathione reductase (GSH-R) and Superoxide dismutase (SOD)), had been measured in studied groups[non pregnant women],group B-I[first trimester], group B-II[second trimester who used folic acid supplementation regularly 5 mg daily] and group B-III [second trimester who used folic acid supplementation irregularly].Results: The level of transferrin, adenosine deaminase (ADA), malondialdehyde (MDA) and uric acid showed significant increase by comparing group B-II and group B-III] ,also when compared to [non pregnant women],group B-I.Iron, Total antioxidant capacity (TAC), Glutathione (GSH), Glutathione peroxidase (GSH-Px), Glutathione reductase (GSH-R) and Superoxide dismutase (SOD) showed significant decrease in group B-II and group B-III when compared to [non pregnant women and group B-I. In conclusion irregular supplementation of folic acid increased indicators of lipid peroxidation in first trimester of pregnancy. Therefore, this regimen of supplemental folic acid may provide excessive amounts of folic acid and appears to increase the risk of oxidative stress. Key words: Folic acid, lipid peroxidation, adenosine deaminase ,antioxidants, transferrin, Iron and pregnancy .